DOWER PAYMENT TO A WIFE (MAHR) BY HER HUSBAND UNDER THE SYRIAN PERSONAL STATUS LAW OF 1953 AND SOME OTHER FAMILY LAWS IN ARAB COUNTRIES - Obaid, Ehab (Gênero & Direito, 2020)
The article considers the issue of dower, which is paid by the husband to his wife and appears as one of the husband’s liabilities according to the provisions of the Syrian Personal Status Law of 1953, as well as under some other Arab family laws. The presented study examines the views of known Islamic jurisprudence schools on this issue, given that the 1953 Syrian family law, along with most of the Arab family laws, were acquired from Islamic Sharia law. The author also analyzes some decisions regarding the dower ruled by the Sharia Chamber of the Syrian Court of Cassation. The article also reviews the provisions of valid and invalid marriages in order to determine the amount of the marriage portion payment that a husband is liable to pay.